Prioritisation of green agile workforce enablers from the perspective of sustainable agile supply chain using DANP. (2nd January 2023) - Alavi, Somaieh
Achieving agility and supply chain sustainability requires trained human resources who not only have agility but also are green. The present study aims to prioritise the green agile workforce activities based on the agile and sustainable supply chain. The present study can be considered as the first research in introducing a green agile workforce and its enablers. After an in-depth review of the research literature, the components of the agile supply chain and sustainable supply chain were identified, and the components of the green agile workforce were introduced. Then, using DEMATEL, the communication network among the components was identified and the components of the green agile workforce were prioritised by fuzzy analytic network possess (FANP). Finally, green agile workforce enablers were classified into three main categories: green leadership, green knowledge and skill, and green environment. Also, the results of FANP showed that among green agile workforce enablers, green leadership, green knowledge, and skill, and green work environment were ranked first to third, respectively.